Potentiating cutaneous wound healing in young and aged skin with nutraceutical collagen peptides. (14th September 2020) - Mistry, K.; van der Steen, B.; Clifford, T.; van Holthoon, F.; Kleinnijenhuis, A.; Prawitt, J.; Labus, M.; Vanhoecke, B.; Lovat, P. E.; McConnell, A.
Summary: Background: Chronic wounds continue to be a burden to healthcare systems, with ageing linked to increased prevalence of chronic wound development. Nutraceutical collagen peptides have been shown to reduce signs of skin ageing, but their therapeutic potential for cutaneous wound healing remains undefined. Aim: To determine the potential for nutraceutical collagen peptides to promote cutaneous wound healing in vitro in the context of age. Methods: The potential for bovine‐ or porcine‐derived nutraceutical collagen peptides to promote wound healing of primary cutaneous fibroblasts and keratinocytes derived from young and aged individuals in vitro was assessed by two‐dimensional scratch and cell‐viability assays and by immunofluorescence for the cell proliferation marker, Ki67. The achievement of peptide concentrations in vivo, equivalent to those exerting a beneficial effect on wound healing in vitro, was confirmed by pharmacokinetic studies of hydroxyproline, a biomarker for collagen peptide absorption, following peptide ingestion by healthy individuals over a wide age range. Results: Results demonstrated significant nutraceutical collagen peptide‐induced wound closure of both young and aged fibroblasts and keratinocytes, mediated by enhanced cellular proliferation and migration. Analysis of blood levels of hydroxyproline in young and aged individuals following porcine collagen peptide ingestion revealed peak serum/plasma levels after 2 h at similar concentrations to those exerting beneficial effects on wound healing in vitro . Conclusion: These data demonstrate the capacity for nutraceutical collagen peptides to promote cutaneous wound closure in vitro, at pharmacologically achievable concentrations in vivo, thereby offering a potential novel therapeutic strategy for the management of cutaneous wounds in young and aged individuals.